FGF8 induces epithelial-mesenchymal transition and promotes metastasis in oral squamous cell carcinoma - Hao, Yilong (Int J Oral Sci, 2021)
Oral squamous cell carcinoma (OSCC) is one of the most common cancers worldwide, and with 354 864 new cases each year. Cancer metastasis, recurrence, and drug resistance are the main causes to cripples and deaths of OSCC patients. As potent growth factors, fibroblast growth factors (FGFs) are frequently susceptible to being hijacked by cancer cells. In this study, we show that FGF8 is upregulated in OSCC tissues and high FGF8 expression is related with a set of clinicopathologic parameters, including age, drinking, and survival time. FGF8 treatment enhances the invasive capability of OSCC cells. Lentivirus-based FGF8 expression promotes OSCC metastasis in a mouse lung metastasis model. Further, mechanistic study demonstrates that FGF8 induces epithelial–mesenchymal transition (EMT) in OSCC cells. These results highlight a pro-metastatic function of FGF8, and underscore the role of FGF8 in OSCC development.